Struktur dan Komposisi Vegetasi Mangrove di Kawasan Pesisir Pulau Sebatik, Kabupaten Nunukan, Kalimantan Timur - Ardiansyah, Windy Indra; Pribadi, Rudhi; Soenardjo, Nirwani (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Sebatik Island is one of the main habitat of mangrove ecosystems in Indonesia. Based on the function, one of the mangrove forest resources with huge potential. Mangrove communities occupy the area between land and sea that have environmental conditions differ from one another. This is interesting because the management is still encountered some problems such as the conversion of mangrove forest as an area of fishpond, housing and other interests. The purpose of this study to determine the structure and composition of mangrove vegetation in Coastal Areas of Sebatik Island, Nunukan regency, East Kalimantan. The study was conducted at five locations on the island of Sebatik, the River Stake, Cape Coral, Balansiku, Setabu and Bambangan, each site is divided into 9 transects. Vegetation data retrieval done by the method of sampling survey. Each transect sampling plot made. Each individual tree (plot 10 m x 10 m) and Sapling (subplot 5 m x 5 m) were identified and measured diameter at breast height (Â± 1.3 m). While the calculated number of seedlings of each species and the percentage of closure (plots 1 mx 1 m). Mangrove area. The results indicate the presence of 19 species of mangrove species that fall into 14 families were found at the sites. In general, vegetation of mangrove tree is dominated by Sonneratia alba in Sebatik Island with Importance Value (IV) range from 86.83 - 171.43 % and density 500 ind/ha - 2000 ind/ha, except Bambangan which dominated by Rhizophora apiculata 86.52% and density 100 ind/ha. Sapling category, dominated by species of Sonneratia alba in Balansiku and Setabu with IV 136.65 % and 67.65 % with a density 3200 ind/ha and 1600 ind/ha. Sungai Pancang is dominated by species Avicennia alba with IV 81.64 % and density 2000 ind/ha, Tanjung Karang dominated by species Rhizopohora mucronata with IV 59.24% and density 1200 ind/ha, and Bambangan dominated by species Rhizopohora apiculata with IV 82.76% and density 2000 ind/ha. Seedling category, dominated by species of Sonneratia alba in the Sungai Pancang and Setabu with IV 107.15% and 72.79% with a density 30 000 ind/ha and 60 000 ind/ha, Tanjung Karang and Bambangan dominated by species of Rhizophora apiculata with IV 115.55 % and 136.53% and density 50 000 ind/ha and 150 000 ind/ha. species diversity and evenness was average.